2004
DOI: 10.1002/ajim.20097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the size and type of free particulates collected from unused asbestos‐containing brake components as related to potential for respirability

Abstract: We conclude that any manipulation of new asbestos containing brake components would be expected to yield free dust containing chrysotile asbestos of respirable size. That the vast majority of these fibers and particulates would not be counted as regulated fibers rendering assessment of potential exposures in the work place, based on data of Permissible Exposure Limits or Regulated Fibers, questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…At one point asbestos was a serious issue in the composition of brake dusts [75] but in 1986, the U.S. EPA placed a ban on the use of asbestos in brakes. The U.S. EPA required that new transportation vehicles have asbestos-free brakes by September 1993 [76].…”
Section: Classification Compositionsmentioning
confidence: 99%
“…At one point asbestos was a serious issue in the composition of brake dusts [75] but in 1986, the U.S. EPA placed a ban on the use of asbestos in brakes. The U.S. EPA required that new transportation vehicles have asbestos-free brakes by September 1993 [76].…”
Section: Classification Compositionsmentioning
confidence: 99%
“…While the study by Weir and Meraz provided insight into the types of particles found within the debris, they did not seek to isolate and characterize the more relevant respirable fraction of the debris or crucially, the number of classifiable fibers present (based on the WHO definition, WHO 1997). A later study by Atkinson et al (2004) evaluated the size and type of free particulates collected from chrysotile-containing brake components using TEM. However, whereas Weir and Meraz simulated grinding and drilling of the brake pads to generate particulates, Atkinson rinsed the unused brake pad to recover any loose surface debris.…”
Section: Release and Characteristics Of Chrysotile-containing Brake Dmentioning
confidence: 99%
“…The use of phase contrast microscopy (PCM), which is used to establish a permissible exposure limit (PEL), is incapable of detecting small asbestos fibers that are nevertheless potentially capable of causing disease. Our ''theoretical'' classification [ (Table I), Atkinson et al, 2004] of which asbestos structures in each group indicate which would be included in a PCM count as well as what would be 'missing' fibers. From the beginning what we did realize was that the literature contains abundant data, including data from our own studies, which indicate that the detection of chrysotile fibrils, most thinner bundles, and individual fibers of many amphiboles require the use of an analytical transmission electron microscope (ATEM) applied at a sufficiently high magnification to permit their recognition.…”
Section: To the Editormentioning
confidence: 99%